the Algerian Administration Between Reform and Development - bourouis, adel; ghazali, adel (Journal of Social Sciences and Humanities, 2024)
The bureaucratic apparatus constitutes a locomotive for development in all societies through the optimal exploitation of capabilities and resources and an attempt to develop them at another stage. It is not possible to imagine the outputs of the development process in light of an administrative apparatus that suffers from defects in its parts, which is reflected in the performance of its functions objectively. This is what applies at least to the reality of the administration. The Algerian woman, who does not meet the difference, as she suffers from negative symptoms that are reflected in the public service she provides The fact that it needs a deep reform that includes both the structural and functional aspects. Hence, the current study, through its use of the descriptive approach, tries to identify the most important diseases that necrosis the body of the Algerian administrative apparatus and try to provide some solutions that enable them to overcome this situation